Essentialism, antihaecceitism, and haecceitism - Lenart, Karol (Hybris, 2019)
A standard contemporary formulation essentialism defines essential properties with a help of a concept of possible worlds. It is often argued that in order to use possible worlds effectively, facts about transworld identity of individuals need to be determined. In this paper I discuss how essentialist might attempt the issue of transworld identity of individuals. Specifically, I analyze a connection between essentialism and the two theories that explain the transworld identity issue, that is, haecceitism and antihaecceitism. I provide a detailed analysis of different variants of antihaecceitism and argue, that all of them are incompatible with basic intuitions that stay behind essentialism. In contrast to that, I defend a position that essentialism ought to be combined with some form of haecceitism. In the remainder of this paper I provide the two ways through which essentialist might be a haecceitist.